Leituras do processo de criação do romance Nhô Guimarães de Aleilton Fonseca - Santos, Adna Evangelista Couto dos (2012)
Readings from the process of creating of romance Nho Guimarães, bahian writer Aleilton Fonseca. This is the first work of master's thesis on the writer and his work. Was sought through this, take a reading of the genetic process of creation in Nho Guimarães, in order to, to design a broader perspective on the profile of the writer and the perception of the work of writing and the multiple possibilities and movements that can display text, thus showing all their mobility and dynamic. It presents a brief history of the fields of knowledge guiding this work. Philology was elected as a place of speech, however, for the treatment of the subject matter, literary text, was used as methodology the perspective of genetic criticism. There was a study on the life and work of the writer, the run of his career, his role in academic life and how their experiences influenced the construction of the works he wrote, thus aiming to promote the representation of bahian writer in the scenario literature nationally and globally. Then follows the study of the process of creating Nhô Guimarães focusing the genesis of the work, the change of gender in the process of textual construction, intertextuality in view of the literary text and analysis of the most frequent genetic movements that shape the process of creating of romance. The dossier's genetic work is composed of eight witnesses digitoscritos with characteristics of autograph manuscripts and printed one, the only published edition of the book.